Utilization of rice straw biochar and urea to mitigate greenhouse gases emission in sustainable rice production - Lai, Lai (2018)
The agricultural sector generally emits three main greenhouse gases (GHGs) to the atmosphere, namely, nitrous oxide (N2O), methane (CH4) and carbon dioxide (CO2). For sustainable rice production and soil health, the application of mineral fertilizers along with organic fertilizers under mitigation option for climate change is of concern. Hence, the present study was undertaken to determine how the effect of rice straw biochar (BC) and urea management can mitigate GHG emission to ensure sustainable rice production. Three pot experiments were conducted in a randomized complete block design with four replications. The first pot experiment consisted of treatments with rice straw BC (9 t/ha) and different rates of urea (30, 60, 90, 120 and 150 kg N/ha) and a control of 150 kg N/ha to determine the effect on GHG emission and soil fertility in rice production. The increased % of grain yield over control (20.7, 21.2 and 21.1%) were found in treatments BC+ 60, 90 and 120 kg N/ha respectively. The lowest combined global warming potential (GWP) by CH4 and N2O (46788 kg CO2-eq/ha) was recorded in treatment, BC + 30 kg N/ha and followed by BC + 60 kg N/ha which had 50751kg CO2-eq/ha. Improved soil properties and higher nutrient (P, K and Mg) uptake were also observed in all BC treatments (except BC+ 30 kg N/ha) although there was no consistency among the BC treatments. The application of rice straw BC (9 t/ha) through 60 kg N/ha is proposed for increasing yield, improving soil properties and reduced GHG emission in relative to control. The second pot experiment was conducted to determine the persistent effect of rice straw BC (9 t/ha) on GHG and soil fertility by the same treatments as the first, but without additional nutrient. Although control itself had lower yield (34.7%) than optimum from the first experiment, increased grain yield over control (%) at 4.2, 5.1, 14.5 and 19.7% in treatments BC+60, 90, 120, 150 kg N/ha respectively were recorded. The lower GWP by CH4 (219.6- 244.4 kg CO2-eq/ha) was estimated in all BC treatments relative to control (361.5 kg CO2-eq/ha) due to reduced methane gas emission regardless of rate of urea. Soil parameters, CEC and residual nutrients such as, P, K, Cu, Fe and Mn were consistently higher in all BC soil relative to control. In terms of food security in the residual BC soil, some extent of supplemental fertilizer should be considered although residual rice straw BC (9 t/ha) had positively persistent effect over control. The third pot experiment was carried out to determine the most feasible rate of rice straw BC by applying with optimum rate of urea. Treatments comprised of different rates of rice straw BC (9, 8, 7, 6, and 5 t/ha) + 60 kg N/ha, control (150 kg N/ha) and 60 kg N/ha. Increased % of grain yield over control (14-16%) were found in rice straw BC (9, 8, 7 and 6 t/ha + 60 kg N/ha) regardless of rates of BC. Lower combined GWP (by CH4 and N2O) (44438- 45640 kg CO2-eq/ha) were amounted in all BC treatments irrespective of rates of BC. Improved soil properties except P and Ca were observed in all BC soil. Besides, major nutrients, N, P, and K uptake were higher in all BC plants. The mechanism of effect of BC on reduced N2O emission was due to significantly reduced nitrite concentration in BC (6 t/ha) + 60 kg N/ha over control (150 kg N/ha) in which NO2 - (conc) was highly correlated with the absorbance of bacteria, Nitrosomonas europaea. Thus, the present study proposes that rice straw BC (6 t/ha) + 60 kg N/ha should be recommended for sustainable rice productivity. Although this research was limited to pot and there was no nutrient leaching losses, the synergetic effect of rice straw biochar and reduced rate of urea was worth mentioning for acidic paddy soil. Field experiment of this organic soil amendment should be conducted to demonstrate and transfer technology to farmers.